Circadian Fluctuations of Plasminogen Activator Inhibitor and Tissue Plasminogen Activator Levels in Plasma of Patients with Unstable Coronary Artery Disease and Acute Myocardial Infarction - Huber, Kurt; Rosc, Danuta; Resch, Irene; Schuster, Ernst; Glogar, Dietmar H; Kaindl, F; Binder, Bernd R (Thrombosis and Haemostasis, 1988)
A decrease in the fibrinolytic potential, mainly due to an elevation of plasminogen activator inhibitor (PAI), has been described in patients with stable coronary artery disease and a previous myocardial infarction. We investigated plasma levels of PAI and tissue plasminogen activator (t-PA) and their possible circadian variations in patients with unstable coronary artery disease (CAD). Sixty-three patients were studied for at least 2 consecutive days during their stay at the coronary care unit (CCU). Diurnal plasma fluctuations in PAI and t-PA and onset of further myocardial ischemic episodes were monitored. As controls we used 22 age-matched patients submitted to the clinic because of non cardiac chest pain or valvular disease who revealed no evidence of CAD. PAI levels were significantly elevated in patients with unstable CAD (p < 0.0001) but were not influenced by the extent of underlying CAD, history of previous myocardial infarction, known risk factors for CAD, or by extent of myocardial damage. The circadian variation of PAI levels with peak values between midnight and 6 A. M. found in controls was still present in patients but at a higher level. Preservation of circadian pattern in PAI plasma levels despite myocardial ischemic attacks indicates that elevation of PAI is rather not caused by a reactive phenomenon. On the other hand, elevated PAI levels and episodes of severe myocardial ischemia exhibiting a median time of onset at 10 A. M. seem to be closely related.
Keywords: Circadian variation; Tissue plasminogen activator; Plasminogen activator inhibitor; Unstable coronary artery disease